2013
DOI: 10.1002/hep.26594
|View full text |Cite
|
Sign up to set email alerts
|

High-fat and high-sucrose (western) diet induces steatohepatitis that is dependent on fructokinase

Abstract: Fructose intake from added sugars has been implicated as a cause of nonalcoholic fatty liver disease. Here we tested the hypothesis that fructose may interact with high fat diet to induce fatty liver, and to determine if this was dependent on a key enzyme in fructose metabolism, fructokinase. Wild type or fructokinase knockout mice were fed a low fat (11%), high fat (36%) or high fat (36%) and high sucrose (30%) diet for 15 weeks. Both wild type and fructokinase knockout mice developed obesity with mild hepati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
209
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 270 publications
(228 citation statements)
references
References 32 publications
14
209
2
3
Order By: Relevance
“…Moreover, we also showed that all these effects are mediated by KHK-dependent metabolism of fructose in the liver, which is, as we demonstrated in the current study and previously (10), a highly specific feature of obesity and the metabolic syndrome induced by fructose consumption. KHK deficiency does not protect from fructose-independent obesity, such as high-fat diet (39). Interestingly, KHK-C expression is upregulated in fructose-induced obesity Differences between the levels of the adiponectin mRNA in WT and KHK-A/C-KO mice are not confirmed (P = 0.07).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, we also showed that all these effects are mediated by KHK-dependent metabolism of fructose in the liver, which is, as we demonstrated in the current study and previously (10), a highly specific feature of obesity and the metabolic syndrome induced by fructose consumption. KHK deficiency does not protect from fructose-independent obesity, such as high-fat diet (39). Interestingly, KHK-C expression is upregulated in fructose-induced obesity Differences between the levels of the adiponectin mRNA in WT and KHK-A/C-KO mice are not confirmed (P = 0.07).…”
Section: Discussionmentioning
confidence: 91%
“…(10), which amplifies the detrimental effects of fructose even more, and in obesity caused by Western diet (high fat/high sucrose) (39) with fructose present in the form of a dimer with glucose, but it does not respond to obesity caused by fructose-independent mechanisms, such as highfat diet (39). Our results also suggest that direct effects of fructose on the adipose tissue via either KHK-A, which is a low-activity KHK isoform expressed in adipocytes (5), or the adipose-specific version of hexokinase, which actively metabolizes fructose (11), or via KHK-C, which is expressed at a minuscule level in white adipose tissue (Supplementary Table 1), are less important.…”
Section: Discussionmentioning
confidence: 99%
“…[132][133][134] One of the consequences of the studies on fructose metabolism is the recognition that it is not the caloric content that matters as much as whether ATP depletion occurs, the latter being primarily governed by the concentration of fructose that hits the liver. 108,118,135 This provides strong reasoning why soft drinks and sugary beverages may be so tightly associated with the development of obesity, metabolic syndrome, diabetes, and cardiovascular disease, 132,[136][137][138][139][140][141][142][143][144][145][146][147][148][149] as sugary beverages are often highly concentrated in fructose and are frequently ingested rapidly.…”
Section: The Rise In Intake Of Added Sugars and Their Effect On Africmentioning
confidence: 99%
“…The pathogenic mechanisms related to intrahepatic fat content induced by fructose consumption are related to an imbalance among fatty acid synthesis, betaoxidation and triglyceride outflow from the liver [24]. Indeed, the direct comparison between saturated fats-and fructose-rich diets revealed that these two dietary components differently affect liver lipid metabolism, with fructose enhancing both beta-oxidation and fatty acids export, counteracted by a strong activation of lipogenesis and palmitate production [40].These conditions trigger an imbalance of normal redox state of cells that makes the liver more susceptible to inflammation and thus to progression of NAFLD to non-alcoholic steatohepatitis (NASH) [40,41].…”
Section: Lipogenic Effect Of Fructosementioning
confidence: 99%